2013
DOI: 10.1016/j.gene.2012.11.041
|View full text |Cite
|
Sign up to set email alerts
|

Human TNFα-induced protein 3-interacting protein 1 (TNIP1) promoter activation is regulated by retinoic acid receptors

Abstract: Coregulator proteins play key roles in transcriptional control by members of the nuclear receptor superfamily. Previously, we demonstrated that tumor necrosis factor α (TNFα)-induced protein 3-interacting protein 1 (TNIP1) is a corepressor of agonist-bound retinoic acid receptors (RARs). Additionally, TNIP1 has been shown to repress peroxisome proliferator-activated receptors (PPAR) and NF-κB activity and interact with HIV proteins nef and matrix. TNIP1 transcriptional regulation, however, is under studied. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…The TNIP1 promoter contains retinoic acid response elements (RARE) and retinoid-acid-receptor binding sites. These elements are involved in the induction of TNIP1 expression by retinoic acid under permissive epigenetic conditions in different cell lines ( 19 ). Since ATRA is an effective drug used for acne treatment, we examined whether this compound is capable of regulating TNIP1 and, thus, the expression of downstream targets of the TLR signaling pathway in keratinocytes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The TNIP1 promoter contains retinoic acid response elements (RARE) and retinoid-acid-receptor binding sites. These elements are involved in the induction of TNIP1 expression by retinoic acid under permissive epigenetic conditions in different cell lines ( 19 ). Since ATRA is an effective drug used for acne treatment, we examined whether this compound is capable of regulating TNIP1 and, thus, the expression of downstream targets of the TLR signaling pathway in keratinocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies found functional RARE elements in the TNIP1 promoter region, and that TNIP1 was induced by ATRA in HeLa cells under permissive epigenetic conditions, in the presence of Trichostatin A co-treatment ( 19 ). Trichostatin A inhibits histone deacetylase I and II and alters gene expression by opening chromatin and allowing transcription factors to bind, thus, promoting transcription of different genes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Among these proteins, dystrophin (DMD), which has different isoforms expressed in muscle and in brain, plays a role in synapse structure and function . TNFAIP3‐interacting protein (TNIP1) is a corepressor of agonist‐bound retinoic acid receptors (RARs) and a regulator of nuclear factor κB (NF‐kB) pathway . This protein has been identified in exosomes from patients with neural tube defects .…”
Section: Resultsmentioning
confidence: 99%
“…To examine the impact of PRMT3-ALDH1A1 interaction on gene-expression regulation by RA in vivo, we measured the mRNA levels of RA-responsive genes [39][40][41][42][43][44][45] involved in diverse biological processes (Supplementary Table 2) (i) with or without overexpressing wild-type PRMT3 or PRMT3-E338Q mutant, (ii) with control siRNA or PRMT3 specific siRNA and (iii) in the presence or absence of RALD using quantitative RT-PCR (Fig. 6 and Supplementary Fig.…”
Section: A L D H 1 a 2 A L D H 1 Amentioning
confidence: 99%